Utilization, barriers and benefits of non-pharmacological practices in acute pain relief among surgical patients at Hospital Universiti Sains Malaysia (Hospital USM) - Sulaiman, Suziana Rosaini
The utilization of non-pharmacological practices is a very crucial component in postoperative pain management in pain relief. This study was designed to determine the utilization, barriers and benefits of non-pharmacological practices; examined the relationship between pain level with the practices and the difference in utilization of nonpharmacological practices between age, gender and educational level in acute pain relief. Hundred patients from surgical wards were randomly selected. Data were collected from January to March 2013 using self administered questionnaires and analyzed using SPSS version 19 for frequency, percentage, mean, standard deviation, p value and correlation coefficient. Ethical approval was obtained from Research Ethics Committee (Human), USM. Most of surgical patients had moderate pain level on the first 24 hours after surgery. They sometimes utilized non-pharmacological practices and mostly prefer to practice physical method such as massage and positioning. Mostly they not knowing the correct way in utilizing it and claimed that the pain will be reduced. There was poor relationship between pain levels with the utilization of non-pharmacological practices (r= 0.17). There were significant difference in deep breathing exercise (p= 0.036) and distraction (p-0.023) between age group; and in deep breathing exercise (p=0.007) and massage (p-0.024) between education level and no significant difference in any non pharmacological practices between gender. Thus, utilization of non-pharmacological practices should be implemented in the wards for better pain management.